A New Computer-assisted Literary Criticism? - Siemens, Raymond G. (Computers & the Humanities, 2002)
If there is such a thing as a new computer-assisted literary criticism, its expression lies in a model that is as broad-based as that presented in John Smith's seminal article, ``Computer Criticism,'' and is as encompassing of the discipline of literary studies as it is tied to the evolving nature of the electronic literary text that lies at the heart of its intersection with computing. It is the desire to establish the parameters of such a model for the interaction between literary studies and humanities computing – for a model of the new computer-assisted literary criticism – that gave rise to the papers in this collection and to the several conference panel-presentations and discussions that, in their print form, these papers represent.